FLEX a flexible extension and integration concept for software development in KORSO and COMPASS - Ehrig, Hartmut 1944-2016 (Techn. Univ. Berlin, Fachbereich 20, Informatik, 1993)
Abstract: "Motivated by the experience within the ESPRIT BR WG COMPASS and the BMFT-project KORSO (Korrekte Software) we propose a flexible extension and integration concept for software development, called FLEX. In addition to support software development by formal methods the aims of FLEX are mainly to allow a smooth change from classical semi- formal techniques for software development to formal techniques with flexible tool support for all levels of development. These aims lead to a number of requirements for FLEX which are already partially supported by concepts availabe in the literature, while several other aspects concerning extension and integration of different subtechniques and languages still have to be investigated. To meet these aims and requirements a general and first specific tasks are defined and it is shown how far recent publications in the area of algebraic specifications are contributions for these tasks already. The general task according to FLEX -- which is considered to be a long term project -- is to provide generic language, tool and methodology development for KORSO and COMPASS in the spirit of development of generic software systems with flexible extension and interconnection mechanisms."
Keywords: Software engineering